2009
DOI: 10.1378/chest.09-0174
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Analysis of High-Resolution CT Scans in Severe Asthma

Abstract: HRCT scan abnormalities are common in patients with severe asthma. Nonradiologic assessments fail to reliably predict important bronchial wall changes; therefore, CT scan acquisition may be required in all patients with severe asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
149
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(162 citation statements)
references
References 39 publications
10
149
2
1
Order By: Relevance
“…High resolution computed tomographic (HRCT) studies of airway structure are providing quantitative morphometry of the airways and distal lung in adults with severe asthma, but less is known in children [115][116][117][118]. In adults, there are relationships to lung function and more severe exacerbation-prone disease.…”
Section: Structural Abnormalitiesmentioning
confidence: 99%
“…High resolution computed tomographic (HRCT) studies of airway structure are providing quantitative morphometry of the airways and distal lung in adults with severe asthma, but less is known in children [115][116][117][118]. In adults, there are relationships to lung function and more severe exacerbation-prone disease.…”
Section: Structural Abnormalitiesmentioning
confidence: 99%
“…The prevalence of bronchiectasis in patients with severe asthma is relatively high; with 25–40% of patients having radiological signs of bronchiectasis [91,92], compared to 3% in a population of generally milder asthma [93]. …”
Section: Systematic Assessment Of Severe Asthmamentioning
confidence: 99%
“…Bronchiectasis per se may cause obstructive airflow limitation [92], and is thus a also a differential diagnosis of asthma [95]. Furthermore, bronchiectasis increases the susceptibility to infections [95].…”
Section: Systematic Assessment Of Severe Asthmamentioning
confidence: 99%
“…HRCT showed that the airway wall thickening was well correlated with thickening of the RBM as shown by bronchial biopsy, and thickening of the airway wall had a good correlation with the deterioration of pulmonary function. Gupta et al [22] found that HRCT scan abnormalities were present in 80% of subjects with severe asthma and often coexisted with bronchial wall thickening (62%), bronchiectasis (40%), and emphysema (8%). HRCT scans can reliably predict important bronchial wall changes.…”
Section: Discussionmentioning
confidence: 99%